Mechanisms of Pragmatic Focusing in Modern English-Language Versions of the “Canonical” Plot of the Blue Beard - Z. M. Chemodurova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The analysis of the most common mechanisms of pragmatic focusing used by modern English-speaking authors in the reinterpretation of canonical, “roving” plots is proposed. Particular attention is paid to the context as one of the types of foregrounding, possessing ontological salience and realizing text-forming, expressive, evaluative, ludic functions. A comparative structural, compositional, and linguistic-stylistic analysis of eight literary texts intertextually correlated with the classic story of the Blue Beard made it possible to identify such methods of attention distribution in the modeled by A. Carter, D. Bartelmi, J. Updike, J. K. Oates, S. King, M. Atwood, W. Vernon, and F. Block as a ludic mode of formulating narratives, changing narrative perspectives, introducing “text within the text”, meta- fictional commentary. Along with focusing mechanisms, the article also pays attention to the defocusing of some traditional narrative elements, which is believed to be an integral part of the interpretation program of the literary texts under consideration. The authors of numerous versions of the story about Bluebeard, foregrounding various language “games of focus”, highlight the creative transformations of archetypal images and cross-cutting motives that reflect gender, socioeconomic, cultural changes in modern society.